25th Anniversary Article: What Can Be Done with the Langmuir‐Blodgett Method? Recent Developments and its Critical Role in Materials Science. (8th October 2013) - Ariga, Katsuhiko; Yamauchi, Yusuke; Mori, Taizo; Hill, Jonathan P.
<x xml:space="preserve">Abstract</x> The Langmuir‐Blodgett (LB) technique is known as an elegant method for fabrication of well‐defined layered structures with molecular level precision. Since its discovery the LB method has made an indispensable contribution to surface science, physical chemistry, materials chemistry and nanotechnology. However, recent trends in research might suggest the decline of the LB method as alternate methods for film fabrication such as layer‐by‐layer (LbL) assembly have emerged. Is LB film technology obsolete? This review is presented in order to challenge this preposterous question. In this review, we summarize recent research on LB and related methods including (i) advanced design for LB films, (ii) LB film as a medium for supramolecular chemistry, (iii) LB technique for nanofabrication and (iv) LB involving advanced nanomaterials. Finally, a comparison between LB and LbL techniques is made. The latter reveals the crucial role played by LB techniques in basic surface science, current advanced material sciences and nanotechnologies.